2023
DOI: 10.3390/bs13040331
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Gamified Tools for Foreign Language Learning (FLL): A Systematic Review

Abstract: Gamification has emerged as a promising approach for foreign language learning (FLL), which refers to the use of game design elements to engage learners or improve academic performance. However, the features of gamification studies in FLL and their effectiveness are unclear. Additionally, how previous studies measured the effectiveness of gamified FLL tools is not well understood. In this systematic review, this author addressed these questions based on 21 empirical studies. The findings revealed that the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Fourthly, biases may be present due to the method of data collection [ 53 , 54 ]. Specifically, two out of the six items used to measure public-speaking anxiety are phrased in a reverse manner, which could lead to confusion or inaccurate responses from participants.…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, biases may be present due to the method of data collection [ 53 , 54 ]. Specifically, two out of the six items used to measure public-speaking anxiety are phrased in a reverse manner, which could lead to confusion or inaccurate responses from participants.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Abuhmaid [ 26 ], teachers reported that mentors did not have the knowledge to assist them in integrating IWBs into their teaching subjects. The integration of new technologies with pedagogical content has always been a challenge [ [35] , [36] , [37] ]. Teachers require customized training that is closely related to their specific teaching context, and this training should be immediately applicable [ 16 , 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors in [ 38 ] performed a systematic review of using gamification tools for foreign language learning. The authors put focus on understanding the effectiveness of the gamification tools as according to them the features of gamification tools for learning language are not well understood in existing studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The overall mean of sum of participants' feedback scores for using ChatGPT in terms of five aspects were found to be 29.90 out of 50 for SUS, 30.80 out of 40 for usefulness, 43.30 out of 55 for ease of use, 17.50 out of 20 for ease of learning, and 29.70 out of 35 for satisfaction. Furthermore, the (min, max) scores pairs from the participants' responses are (26,35), (31,54), (13,20), (19,38), and (21,35) for the SUS, ease of use, ease of learning, usefulness, and satisfaction, respectively. The SD was found to be 3.00, 7.60, 5.35, 2.36, and 3.88 for SUS, ease of use, usefulness, ease of learning, and satisfaction, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation